Optimizing Early Childhood Reading Abilities: Perceptions of Private Reading Needs Demands - Arfin, Arfin; Hermanto, Hermanto; Nurzaima, Nurzaima; Lilianti, Lilianti; Usman, Usman; Mujiati, Mujiati; La Ndibo, Yaman (Universitas Ahmad Dahlan, 2024)
The optimization of reading skills in early childhood through private reading demands less need. Kindergarten teachers and intuition do not get demands regarding children's reading skills. The method of this research is quantitative research. The population includes 145 kindergarten and early childhood education students in Kendari City. However, 58% of teachers agree that private reading should be implemented in kindergarten / early childhood because the majority of respondents see positive potential in private reading programs and can provide benefits for children's early literacy development, children's reading skills, the potential to increase children's interest in reading, and have a positive effect on children's language development and knowledge.